ACTION, DECISION MAKING, AND DELIBERATIVE SKILLS CONCERNING THE PARTICIPATORY BUDGET IN PORTO ALEGRE - Cuenca Botey, Luis Emilio (2013)
This paper describes and analyzes the deliberative skills of people participating in the Council of the Participatory Budget (COP), the main deliberation council for the participatory democracy in Porto Alegre. Through the ethnographic observation, we are able to describe agents acting in the assembly. Then, we establish a dialogue between the internal and external events of what Marc Abélès called “lieu du politique”.